Presence of Women on Board: Reference to BSE-30 Companies from 2010-2014 - S, Nisa (International Journal of Accounting & Finance Review, 2017)
The need for gender diversity in the board rooms is getting accepted at corporate levels both national and international. Any change which is brought about voluntarily is more effective and long lasting. Gender representation on corporate boards of directors refers to the proportion of men and women who occupy board member positions. Studies have shown that even though there is no real dearth of talent pool, India, comparatively, has significantly a very low percentage of women representation on boards. No one doubts the importance of diversity in boardrooms, especially in improving corporate governance. With the changing demographics of the global workforce and the fact that women will control 75% of discretionary spending by 2028, globally companies cannot underestimate the importance of improving the gender balance on their boards. Women are increasingly becoming a major driver of the economy, both as contributors and as customers; it is appropriate that they be a part of the team leading companies. Past researches have shown that boards with more women members act as a motivator to other women employees within the organization. Continuing reliance on existing directors is likely to dilute the quality of board members. Broadening the talent pool by including women directors will help boards get skilled and competent members with a diversity of perspectives and leadership styles who can significantly contribute to board performance. The following study was conducted to assess the presence of women on board in BSE 30 listed companies from 2010 to 2014.